The Mechanism Actions of Astragaloside IV Prevents the Progression of Hypertensive Heart Disease Based on Network Pharmacology and Experimental Pharmacology - Jing, Haoran; Xie, Rongsheng; Bai, Yu; Duan, Yuchen; Sun, Chongyang; Wang, Ye; Cao, Rongyi; Ling, Zaisheng; Qu, Xiufen (Frontiers in Pharmacology, 2021)
Background: Astragaloside IV (AS-IV) has been used to treat cardiovascular disease. However, whether AS-IV exerts protection effect against hypertensive heart disease has not been investigated. This study aimed to investigate the antihypertensive and cardioprotective effects of AS-IV on L-NAME-induced hypertensive rats via network pharmacology and experimental pharmacology. Method: The network pharmacology and bioinformatics analyses were performed to obtain the potential targets of AS-IV and hypertensive heart disease. The rat hypertension model was established by administrated with 40 mg/kg/day of L-NAME for five weeks. Meanwhile, hypertension rats were intragastrically administrated with vehicle or AS-IV (40 mg/kg/day) for five weeks. Cardiovascular parameters (SBP, DBP, MAP, HR, and body weight), cardiac marker enzymes (CK, CK-MB, and LDH), cardiac hypertrophy markers (ANP and BNP), endothelial function biomarkers (NO and eNOS), inflammation biomarkers (IL-6 and TNF-α) and oxidative stress biomarkers (SOD, MDA, and GSH) were measured and cardiac tissue histology performed. Results: Network pharmacological analysis screened the top 20 key genes in the treatment of hypertensive heart disease treated with AS-IV. Besides, AS-IV exerted beneficial effect on cardiovascular parameters. Moreover, AS-IV alleviated cardiac hypertrophy via down-regulating the expression of ANP and BNP and improved histopathology changes of cardiac tissue. AS-IV could improve endothelial function via the up-regulation of eNOS expression, alleviate oxidative stress via increasing antioxidant enzymes activities, and inhibit inflammation via down-regulating IL-6 and TNF-α expression. Conclusion: Our findings suggested that AS-IV is a potential therapy drug to improve L-NAME-induced hypertensive heart disease partly mediated via modulation of inflammation and oxidative stress.